Leveraging the experiencescape for destination attractiveness: empirical insights from casino resorts - Brian Garrod (Journal of Hospitality and Tourism Insights, 2024)
Purpose: The experiencescape is a relatively new concept, and research using it remains scarce.This study contributes to the understanding of the experiencescape and its role in tourismconsumption by constructing a novel conceptual model of the experiencescape elements of acasino resort visit and their effects on its attractiveness. Design/methodology/approach: Partial least squares structural equation modelling wasemployed, using data collected from 491 casino resort visitors in Macao, to establish a linkbetween the experiencescape and visitors’ perceived overall attractiveness of the casino resortthrough the mediating effect of arousal. Findings: The findings establish the relationship between experiencescapes and the perceivedoverall attractiveness of integrated casino resorts through the mediating effect of arousal. Originality: This study presents novel insights into the role of emotions in an integrated casinoresort context. It identifies a set of strategies through which managers can increase theattractiveness of their resorts by stimulating customers’ emotions. Practical implications: Casino resort executives are advised to orchestrate various experienceelements from the perspective of the experiencescape to trigger positive tourism experiences.Specifically, all factors related to tangible, gaming and non-gaming, and social experientialstimuli need to be continually reviewed, improved, and innovated.